Developing a content-differentiated mathematics teaching module for vocational high school students: Validity, practicality, and effectiveness - Kanisius Mandur; Fulgensius Efrem Men; Jumadi Jumadi; Agung Wahyu Hermansyah; Rahayu Fuji Astuti (Jurnal Pendidikan Vokasi, 2026)
The increasing diversity of students' learning readiness, interests, and learning profiles requires mathematics instructional materials that support differentiated learning in vocational education. However, teaching modules specifically designed to facilitate content differentiation remain limited. Unlike conventional mathematics modules that primarily provide uniform instructional content, the module developed in this study explicitly incorporates content differentiation to accommodate variations in students' learning readiness, interests, and learning profiles within vocational education settings. This study aimed to develop and validate a content-differentiated mathematics teaching module that is valid, practical, and effective for vocational high school students. A Research and Development (R&D) approach employing the ADDIE instructional design model (analysis, design, development, implementation, and evaluation) was adopted. The module was evaluated through expert validation involving material, media, and language specialists, while its practicality was assessed using teacher and student response questionnaires. Effectiveness was examined through pretest–posttest achievement data. The findings indicated that the developed module achieved a very high level of validity, with material, media, and language validity scores of 87.47%, 90.00%, and 83.33%, respectively. The module was also perceived as highly practical by teachers (93.65%) and students (87.54%). Furthermore, the implementation of the module significantly improved students' mathematics achievement, as reflected by the increase in the mean score from 64.52 (pretest) to 87.65 (posttest) (p < .001). These findings demonstrate that the proposed module provides an effective instructional resource for implementing content differentiation in heterogeneous mathematics classrooms and offers practical support for promoting adaptive and inclusive learning in vocational high schools.